DNA barcoding of endangered peninsular Malaysian slipper orchids, the genus Paphiopedilum - Rajaram, Micheal Charles (2018)
Paphiopedilum is a genus of the orchid family that is highly prized for its beautiful and long lasting flowers. Due to its attractiveness, many plants have been collected from the wild to meet the demands of the market and thus reduced the populations till the point of endangerment. Thus, all Paphiopedilum are protected by CITES Appendix I. Even though they produce beautiful and distinctive flowers, the vegetative form of this genus, however, lacks sufficient distinguishing features that enable species discrimination, creating a problem for accurate species identification for biodiversity inventory and in regulating the control of its trade. DNA barcoding uses standardized regions of DNA that can supplement the current taxonomic identification data. Five species have been identified to occur in Peninsular Malaysia and IUCN Redlist categorized all species as Endangered. Some of the threats recognized to affect Paphiopedilum survival in the wild are poaching, deforestation and logging in Malaysia. The samples were collected in localities throughout Peninsular Malaysia. To produce species-specific barcodes, DNA extraction was performed using the CTAB method. Selected barcode regions were amplified using PCR and the protocols were optimized specifically for all barcodes chosen. Amplified products were sequenced using Sanger bi-directional sequencing method. rbcL and matK has the highest sequence quality and followed by trnH-psbA and ITS. Sequences obtained were edited, aligned and its effectiveness was measured by using several approaches: presence of monophyletic groups in Neighbour-Joining trees, barcoding gap (global and local) and BLASTn sequence similarity. matK showed the highest species resolution with 100% correct match in NCBI BLASTn database followed by ITS (52.9%), trnH-psbA (26.3%) and lastly rbcL (23.5%). All barcodes were correct at the genus level. Phylogenetic trees were constructed using the Neighbourjoining method with Kimura-2-parameter metric and supported by 1000 bootstrap replicates in MEGA 6.0. Trees constructed using matK and ITS barcodes grouped similar species into a clade and congruent with currently accepted taxonomy while those constructed with rbcL and trnH-psbA were unable to resolve the differences between the species. Differences between barcode efficiency are attributed to differing molecular rate of evolution of the individual loci. Global barcoding gap exists only in matK sequences but could be the result of sampling bias and may not be a reliable indicator for species delimitation. Local barcoding gap exists for all species studied using matK sequences except between P. barbatum and P. callosum var. sublaeve. The shared similarities and uneven sampling between both species may contribute to the lack of local barcoding gap. Based on the findings of the study, matK is the most suitable barcode for identifying Paphiopedilum species in Peninsular Malaysia. DNA barcoding presents an effective and simple method for species level identification for Paphiopedilum species.